Once-weekly administration of dulaglutide, a glucagon-like peptide-1 receptor agonist, as monotherapy and combination therapy: review of the AWARD studies - Marina V. Shestakova; Ekaterina A. Yudovich (Сахарный диабет)
For the purpose of exploring the development, pharmacology and clinical trial program related to dulaglutide, we conducted a nonsystematic review of dulaglutide, focusing on the AWARD (Assessment of Weekly Administration of LY2189265 [dulaglutide] in Diabetes Assessment) program of randomized, phase 3 studies. Dulaglutide is a glucagon-like peptide 1 (GLP-1) receptor agonist that causes a variety of antidiabetogenic actions by acting on the incretin system. Steady-state plasma concentrations of dulaglutide are achieved between 2 and 4 weeks following a once-weekly administration. The AWARD 1–6 studies were conducted in patients with different treatment needs, ranging from patients with mild diabetes who can be treated with diet management and exercise to patients for whom target glycemic control cannot be achieved with conventional insulin treatment. Changes in HbA1c from baseline to the primary endpoint assessment (primary efficacy outcome) with dulaglutide were generally dose-dependent and significantly greater than those of active comparators and placebos (AWARD 1–5) or non-inferior to the comparators (AWARD 6). The results of secondary outcome measures demonstrated that glycemic control attained with dulaglutide was sustained for long-term and that a greater proportion of patients treated with dulaglutide achieved a target HbA1c level of <7.0% compared with placebo and/or active comparators. Reduction in fasting serum glucose, glucagon levels and body weight after dulaglutide treatment were noted in most AWARD studies. Although treatment-emergent adverse events were common with dulaglutide, the incidence was similar to that of active comparators in most AWARD studies, and serious adverse events were generally infrequent, except in patients with more severe disease or with prolonged therapy. Hypoglycemic and immunogenic events were also infrequent. In patients with type 2 diabetes, dulaglutide improves glycemic control and leads to clinically useful reduction in body weight in a range of treatment settings.